Appraisal of Dimensional Accuracy in Five Brands of Extended Pour Irreversible Hydrocolloid Materials for FDP Impression - Upasana Panda; Mirna Garhnayak; Gunjan Srivastava; Gopal Choudhury; Pradyumna Ku. Sahoo; Sangram Panda (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim. The purpose of this study was to assess and compare the dimensional accuracies of five brands ofextended pour irreversible hydrocolloid materials for fixed dental prosthesis impression.Materials and methods. Impressions of a master stainless steel model were made with five extended pourirreversible hydrocolloids and one addition silicone impression material. A total of ninety impressions(n=90) were made, with fifteen for each group of impression material. The stone dies retrieved fromthese impressions were analysed with Baty-Vision Systems - Venture 3D CNC machine, for dimensionalaccuracies. Comparison of continuous data between two groups was done with the Wilcoxon rank-sum test(Mann Whitney U test) and for more than two groups with the Kruskal Wallis test (? = .05)Results. All six impression materials showed some amount of error. On comparison of the median totalabsolute deviation of the various dimension of stone dies, the accuracies of impression materials in decreasingorder appeared to be Neocolloid >> Affinis >> Coltoprint >> Zelgan >> 3M ESPE >> Plastalgin. On thecontrary, a comparison of the impression materials, in terms of several dimensions of stone dies differingsignificantly from the stainless-steel model, the sequence in terms of accuracy was, Coltoprint > Affinis >3MESPE > Neocolloid > Plastalgin > Zelgan.Conclusions. Based on the dimensional accuracies of the stone dies retrieved from the impressions,Neocolloid was found to be the best impression material with the least possible deviation, followed byColtoprint and Affinis.